2014
DOI: 10.1021/am500947k
|View full text |Cite
|
Sign up to set email alerts
|

Carbazole-Dendrimer-Based Donor−π–Acceptor Type Organic Dyes for Dye-Sensitized Solar Cells: Effect of the Size of the Carbazole Dendritic Donor

Abstract: A series of novel D-π-A type organic dyes, namely, GnTA (n = 1-4), containing carbazole dendrons up to fourth generation as a donor, bithiophene as π-linkage, and cyanoacrylic acid as acceptor were synthesized and characterized for applications in dye-sensitized solar cells (DSSCs). The photophysical, thermal, electrochemical, and photovoltaic properties of the new dyes as dye sensitizers were investigated, and the effects of the carbazole dendritic donors on these properties were evaluated. Results demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 68 publications
(113 reference statements)
1
32
0
Order By: Relevance
“…Thus, carbazole derivatives are used as synthons for preparation of luminophores [7], and branched 3,6disubstituted derivatives of carbazole are applied as building blocks for creation of more complex organic molecules [8]. Compounds of this type are now used for the synthesis of OLEDs because of their high hole conductivity, photochemical stability, and electroconductivity [9][10][11]. The carbazole-based dendrites are shown to act as luminescent gelators for ordered organogels [16,17].…”
mentioning
confidence: 99%
“…Thus, carbazole derivatives are used as synthons for preparation of luminophores [7], and branched 3,6disubstituted derivatives of carbazole are applied as building blocks for creation of more complex organic molecules [8]. Compounds of this type are now used for the synthesis of OLEDs because of their high hole conductivity, photochemical stability, and electroconductivity [9][10][11]. The carbazole-based dendrites are shown to act as luminescent gelators for ordered organogels [16,17].…”
mentioning
confidence: 99%
“…Also, the molar absorption coefficient (e) of the SGT-102 dye was higher than SGT-101 dye due to p-extended conjugation. Unlike expectation, the SGT-103 dye containing the bulky phenothiazine donor group showed a maximum absorption of 484 nm, which was red-shifted by 5 nm, compared to the other dyes, since it has been recently reported that the blue-shifts in solution with the number of the donor groups in the starburst 2D-p-A organic dye would be expected due to the higher ICT energy levels resulting from the increase of donor moieties [20,21]. However, increasing the number of the donor moiety improves the molar extinction coefficients of the ICT absorption peaks of the dyes.…”
Section: Resultsmentioning
confidence: 60%
“…Specifically, their applications in polymer solar cells (PSCs), polymer light‐emitting diodes (PLEDs), and organic field‐effect transistors (OFETs) offer opportunities for a renewable energy supply as well as the development of display and information technologies . To achieve high‐performance organic sensitizers, many studies have focused on improving the following key properties: (i) improving the light harvesting ability and efficiency, (ii) molecular energy level, and (iii) decreasing the charge recombination reactions at the FTO/TiO 2 /polymer/electrolyte interface . In view of the polymer development, these have been mainly done by engineering their molecular structure and at either donor or acceptor moieties.…”
Section: Introductionmentioning
confidence: 99%